Generation of induced pluripotent stem cells as a potential source of hematopoietic stem cells for transplant in PNH patients - Phondeechareon, Tanapol; Wattanapanitch, Methichit; U-pratya, Yaowalak; Damkham, Chanapa; Klincumhom, Nuttha; Lorthongpanich, Chanchao; Kheolamai, Pakpoom; Laowtammathron, Chuti; Issaragrisil, Surapol (Annals of hematology, 2016)
Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired hemolytic anemia caused by lack of CD55 and CD59 on blood cell membrane leading to increased sensitivity of blood cells to complement. Hematopoietic stem cell transplantation (HSCT) is the only curative therapy for PNH, however, lack of HLA-matched donors and post-transplant complications are major concerns. Induced pluripotent stem cells (iPSCs) derived from patients are an attractive source for generating autologous HSCs to avoid adverse effects resulting from allogeneic HSCT. The disease involves only HSCs and their progeny; therefore, other tissues are not affected by the mutation and may be used to produce disease-free autologous HSCs. This study aimed to derive PNH patient-specific iPSCs from human dermal fibroblasts (HDFs), characterize and differentiate to hematopoietic cells using a feeder-free protocol. Analysis of CD55 and CD59 expression was performed before and after reprogramming, and hematopoietic differentiation. Patients’ dermal fibroblasts expressed CD55 and CD59 at normal levels and the normal expression remained after reprogramming. The iPSCs derived from PNH patients had typical pluripotent properties and differentiation capacities with normal karyotype. After hematopoietic differentiation, the differentiated cells expressed early hematopoietic markers (CD34 and CD43) with normal CD59 expression. The iPSCs derived from HDFs of PNH patients have normal levels of CD55 and CD59 expression and hold promise as a potential source of HSCs for autologous transplantation to cure PNH patients.